ANALISIS KESETARAAN GENDER DALAM PENGUATAN KELEMBAGAAN UNIVERSITAS HALU OLEO - Hasan, Abdul; Matoka, Ulfa (JURNAL EKONOMI UHO, 2016)
This study aimed to obtain information on gender equality in  Haluoleo University. Secondary data were obtained from the Personnel and Finance  Board  across the Faculty/Program and Technical Services Unit-Information Technology  Haluoleo University in 2015 period.  The research used  Gender Analysis Pathway.  The result show that  Halu Oleo University have gender bias. The  rate of participation and access of men higer than women  in the institutional elements such as  students, official structurally of faculty and administrative staff, except for Faculty of Pharmacy and  Public Health Faculty.